Säker uppkoppling mot radiostyrda bilar - Dashtestan Nejad, Soroush; Keyvannia, Behroz (My University, 2015)
The application development is a fast growing trend in the past few years. This, however, is not only associated with smartphones, tablets and smart-TV:s but with the automotive industry as well. The development of applications enhances human-vehicle interaction and provides a comprehensive overview of the vehicle and surroundings for the driver. The goal of this project is to increase the safety and security of the integration between external applications with the vehicle infotainment-system. The project scope is limited to send and receive signals from a radio-controlled car. We have successfully implemented a broker service on a test model radio-controlled car. This distributed system makes a secure communication from/to external applications possible. We have tested and verified connection and communication of the nodes. The result of this project can be used to build a secure connection for the automotive industry.
Keywords: Data- och informationsvetenskap; Computer and Information Science